Passados vinte anos: o conceito de consumidor - Aragão, Maria Ligia Satiro (2010)
The present dissertation focuses on the concept of consumer, which is one of the elements in consumer relations, as well as the identification factor in the application of the Consumer s Protection Code. This work also intends to demonstrate in which extend the change in social facts influenced the construction of the legal concept of consumer. Within this new concept, consumers economic facet became the most important aspect in the economic relation. In this new conjuncture, the economic subject is no longer merely a part of the economic process, but assumed a new role as an autonomous subject. Besides that, the legal concept of consumer was inspired by the mentality which places the consumer in the center of the economic relation. The need of protection was then diagnosed by recognizing the current importance of the consumer. The value given by Law to the natural concept of consumer is also brought up, giving to the standard consumer the position of end user. In the construction of the thesis, several scientific works regarding the interpretation, meaning and extension of the standard concept of consumer were revisited, mainly when related to the term "end user". The subjects designated as consumers by the Consumers Protection Code are also going to be presented. Lastly, the jurisprudence of the some Brazilian Tribunals is succinctly analyzed. The purpose of this work is to demonstrate that, after twenty years of the Code s enforcement, a tendency has began, changing the standard meaning of consumer. Or, at least, it has started expanding the range of the concept in order to comply with its constitutional ground: the vulnerability of the group